Multi-Level Regulation in the Telecommunications Sector
XVIII, 299 p.
Keywords: Through a comparison of the telecommunications sectors in four small EU-countries, an outstanding cast of contributors explore how regulatory authorities at international, EU-, national and regional level within and between sectors coordinate their regulatory decisions in order to provide coherent regulation of markets.